2022
DOI: 10.3390/su14031769
|View full text |Cite
|
Sign up to set email alerts
|

Multitemporal Total Coliforms and Escherichia coli Analysis in the Middle Bogotá River Basin, 2007–2019

Abstract: Currently, one of the main environmental problems that need to be addressed is the pollution inflicted upon different ecosystems by anthropic activities. One example of this problem can be seen in the Bogotá River, a major river in the Cundinamarca department of Columbia and the main water source supplying the Bogotá savannah, which reaches the Colombian capital city. The Bogotá River is highly affected by effluents and wastewater of domestic and industrial origin, among others. These pollutants are generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…The fluctuation in E. coli counts during the El Niño period at the White River site could be attributed to the change in rain patterns and the inadequate treatment of wastewater at the White River WWTP. This observation is similar to the one made by Castro Fernández [42], who stated that there is an untreated or inadequate discharge of water into the Bogotá River, leading to the accumulation of sludge and, consequently, E. coli in the river. Castillo et al [43] confirmed that this is a correlation between seasonal effects and the E. coli level that was evaluated in Casacara Rivers.…”
Section: Escherichia Coli (E Coli) Concentration During the Three Ens...supporting
confidence: 88%
See 1 more Smart Citation
“…The fluctuation in E. coli counts during the El Niño period at the White River site could be attributed to the change in rain patterns and the inadequate treatment of wastewater at the White River WWTP. This observation is similar to the one made by Castro Fernández [42], who stated that there is an untreated or inadequate discharge of water into the Bogotá River, leading to the accumulation of sludge and, consequently, E. coli in the river. Castillo et al [43] confirmed that this is a correlation between seasonal effects and the E. coli level that was evaluated in Casacara Rivers.…”
Section: Escherichia Coli (E Coli) Concentration During the Three Ens...supporting
confidence: 88%
“…Castro Fernández [42], who stated that there is an untreated or inadequate discharge of water into the Bogotá River, leading to the accumulation of sludge and, consequently, E. coli in the river. Castillo et al [43] confirmed that this is a correlation between seasonal effects and the E. coli level that was evaluated in Casacara Rivers.…”
Section: Escherichia Coli (E Coli) Concentration During the Three Ens...mentioning
confidence: 99%
“…The paper is entitled "Multitemporal Total Coliforms and Escherichia coli Analysis in the Middle Bogotá River Basin, 2007-2019". With reference to Bogotá River in the Cundinamarca department of Columbia, highly affected by effluents and uncontrolled domestic, industrial, and/or commercial wastewater, in the paper the quality of its water is assessed using microbiological indicators and data provided by the Regional Autonomous Corporation of Cundinamarca, in order to determine the pollution levels and to highlight the importance of implementing new sustainable treatment alternatives aimed at improving water quality [14].…”
Section: The Topics Of the Published Papersmentioning
confidence: 99%
“…Chromium is a heavy metal used in different industries due to its effectiveness in metal alloys and the preservation of leather in the tannery industry; it has led to the exaggerated use of this heavy metal, causing serious environmental, social, and health consequences. An example of this is in the south of Bogotá, Colombia, where the use of Chromium (VI) in more than 350 tannery industries has led to the discharge of Cr (VI), with concentrations of around 1000 mg/L of this heavy metal, causing the deterioration of the Tunjuelo River, leading to its decrease in its ecosystem services to the community surrounding the river [5][6][7]. Among the methods available to treat industrial effluents, adsorption is the most widely used method for wastewater treatment thanks to its low capital cost, versatility, which allows you to remove most contaminants, and ease of regeneration of the adsorbent [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%